Molecular characterization and phylogenetic analysis of Ukrainian isolates of Cucumber mosaic virus based on the partial sequences of three genes - Shevchenko, T.P.; Tymchyshyn, O.V.; Kosenko, I.A.; Budzanivska, I.G.; Shevchenko, O.V.; Polishchuk, V.P. (Вiopolymers and Cell, 2018)
Aim. In the current work, we carried out the phylogenetic analysis of the Ukrainian isolates of Cucumber mosaic virus using incomplete sequences of several viral genes. Methods. ELISA, RT-PCR, DNA sequencing and phylogenetic analysis. Results. The symptomatic samples of plants from different regions of Ukraine were collected and tested for CMV infection. Partial sequences of the genes encoding coat protein, movement protein and 2b protein of four Ukrainian CMV isolates were amplified and analyzed. These isolates were shown to belong to subgroups IA and IB. The coat protein, movement protein and 2b protein gene sequences demonstrated high intragroup homology. For isolates CMV-Ukr-28 and CMV-Ukr-58, the unique amino acid substitutions were detected in 2b protein sequences which were considered independent of the host plant. Conclusions. The isolates of Cucumber mosaic virus which circulate in Ukraine and are described in this study, belong to the most widespread phylogenetic subgroups IA and IB which are also found in other European countries. The obtained data may indicate separate routes of CMV infection, as well as the ongoing virus microevolution in Ukraine. Мета. Провести філогенетичний аналіз українських ізолятів Cucumber mosaic virus з використанням неповних послідовностей декількох генів вірусу. Методи. Імуноферментний аналіз, полімеразна ланцюгова реакція зі зворотною транскрипцією, секвенування ДНК та філогенетичний аналіз. Результати. Зразки рослин із симптомами було відібрано з різних регіонів України та протестовано на наявність вірусу огіркової мозаїки ВОМ. Отримано й проаналізовано нуклеотидні часткові послідовності генів капсидного білка, білків руху та білка 2b чотирьох ізолятів ВОМ. Показано, що ці ізоляти належать до підгруп ІА та ІВ. Відсоток подібності українських ізолятів за нуклеотидними послідовностями генів капсидного білка, білка руху та білка 2b був високим у межах підгруп. Виявлено унікальні заміни у амінокислотних послідовностях білка 2b ізолятів CMV-Ukr-28 і CMV-Ukr-58, які не пов’язані з рослиною-хазяїном. Висновки. Ізоляти вірусу огіркової мозаїки, які циркулюють в Україні та описані в роботі, належать до найбільш розповсюджених філогенетичних груп, які представлені і в інших європейських країнах. Отримані дані можуть вказувати на декілька окремих джерел проникнення ВОМ на територію України, а також на поточну мікроеволюцію ВОМ в Україні. Цель. Провести филогенетический анализ украинских изолятов Cucumber mosaic virus с использованием неполных последовательностей нескольких генов вируса. Методы. Иммуноферментный анализ, полимеразная цепная реакция с обратной транскрипцией, секвенирование ДНК и филогенетический анализ. Результаты. Образцы растений с симптомами были отобраны в разных регионах Украины и протестированны на наличие ВОМ. Получены и проанализированы частичные нуклеотидные последовательности генов капсидного белка, белка движения и белка 2b четырех украинских изолятов ВОМ. Показано, что эти изоляты принадлежат к подгруппам IA и IB. Процент сходства украинский изолятов по нуклеотидным последовательностям генов капсидного белка, белка движения и белка 2b был высоким в пределах групп. Обнаружены уникальные замены в аминокислотных последовательностях изолятов CMV-Ukr-28 и CMV-Ukr-58, не связаные с растением-хозяином. Выводы. Изоляты вируса огуречной мозаики, циркулирующие в Украине и описаные в работе, принадлежат к наиболее распространенным филогенетическим подгруппам IA и IB, которые представлены и в других европейских странах. Полученные данные могут указывать на несколько отдельных источников проникновения ВОМ на территорию Украины, а также на текущую микроэволюцию вируса в Украине.